Analysis of Flood Disaster Adaptation Strategies Among People of Guma Local Government Area, Benue State, Nigeria - Solomon Gbaa (MO.RI Publishing, 2022)
Abstract – One of the most important issues in flood risk management is finding a way to cope with uncertainties. Despite centuries of experience with flood management, flood disasters become more frequent and are increasing in severity due to climate change. This work examined flood disaster adaptation strategies among the people of Guma Local Government Area, Benue State. Data on the demographic characteristics of respondents, flood frequency, duration, and impact of flood disasters on people of the study area, as well as flood mitigation and adaptation strategies, were obtained using a questionnaire. A total of 380 respondents were sampled using random sampling. The data were analyzed using frequencies and percentages and presented in tables. Results revealed that the respondents are susceptible to the impact of flood disasters due to their socio-demographic characteristics. Furthermore, the results show that the frequency of flood disasters is biennial while its duration is between one to two weeks. Flood also impacts both directly and indirectly, involving mostly destruction of farm crops, and disruption of transportation. Lastly, the results show that the respondents mostly clear-filled/blocked drainages around them to mitigate the impact of flood disasters and many of the respondents construct wooden bridges across drainages/gutters in order to adapt to flooding in their areas. The study recommends that non-flood-sensitive economic activities should be embraced to mitigate the impact of flooding in the study area. There should also be public enlightenment and sensitization on the need to adopt both structural and nonstructural measures of adapting to flood disasters as climate change continues to trigger more severe, and frequent floods.